Neuromotor mechanisms of successful football penalty kicking: an EEG pilot study - Li, Dan; Elbanna, Hatem; Lin, Fang-Yi; Lu, Chieh-Ju; Chen, Li-Ju; Lu, Guo; Yu, Chien-Lin; Wang, Kuo Pin (Frontiers in Psychology, 2025)
IntroductionUnderstanding the neuromotor processes underlying successful and unsuccessful performance in lower limb movements, such as football kicking, is essential for athletes. However, further investigation is needed to determine whether lower activation of the prefrontal and central cortices, which are associated with motor programming, such as motor planning and motor control, corresponds to higher degrees of psychomotor performance in a difficult task. To address this issue, this within-subject pilot study aimed to investigate neuromotor processes in skilled football players performing penalty kicks under a difficult condition.MethodsTen skilled football players were recruited and asked to perform 30 kicks under a difficult condition where the target size was adjusted to maintain a kicking success rate between 40 and 60% for each player while we recorded EEG data during motor preparation. Afterwards, EEG power in the 8–13 Hz frequency band was analyzed at frontal (Fz) and central (Cz) regions before action.ResultsThe main result indicated that successful penalty kicks were associated with lower 8-13 Hz power at frontal and central regions before action, suggesting efficient neural activation for motor planning and control during motor preparation.DiscussionThese findings support the model of attention allocation and the psychomotor efficiency hypothesis, aligning with similar neuromotor processes observed in golf studies. Overall, this study highlights the critical role of motor planning and control in successful athletic performance.